1978
DOI: 10.1097/00006842-197805000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Slow Potential (ERSP) Correlates of Thyroid Gland Function Level

Abstract: This study shows an association between thyroid gland function level and event-related slow brain potential (ERSP) parameters (peak amplitude and area under the curve), obtained during "classical" and "operant" reaction-time paradigms. A significant positive correlation between ERSP parameters and 24-hr I131 uptake and a negative nonsignificant one between them and ankle jerk reflex were found. Organismic factors related to thyroid function had greater influence upon ERSP amplitude and area than situational on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Hypothyroidal patients demonstrated the lowest peak values and negative area under the curve of event-related slow potentials compared to both euthyroid and thyrotoxic controls (Lolas, De La Parra, & Gramegna, 1978). Himelfarb, Lakretz, Gold, and Shanon (1981) showed that auditory brain stem responses of hypothyroidal patients were prolonged with diminished amplitude, flattened peaks, and poor synchronization.…”
Section: Hypothyroidismmentioning
confidence: 94%
“…Hypothyroidal patients demonstrated the lowest peak values and negative area under the curve of event-related slow potentials compared to both euthyroid and thyrotoxic controls (Lolas, De La Parra, & Gramegna, 1978). Himelfarb, Lakretz, Gold, and Shanon (1981) showed that auditory brain stem responses of hypothyroidal patients were prolonged with diminished amplitude, flattened peaks, and poor synchronization.…”
Section: Hypothyroidismmentioning
confidence: 94%